Factors that correlate with sleep oxygenation in children with cystic fibrosis - KARADAĞ, BÜLENT TANER (WILEY, 2007)
Objective: Cystic fibrosis (CF) patients may develop hypoxemia during sleep. Limited information is available on nocturnal oxygen saturation in CF children with less severe lung disease. The aim of this study was to investigate the degree of nocturnal oxygen desaturation and factors that correlate with nocturnal oxygenation in CIF children with normal pulmonary function tests (PFTs) or mild to moderate lung disease. Method: Awake resting and post-exercise SPO2 were measured by pulse oximetry. Each patient had overnight oximetry monitorization at home. Six minutes walk test (6MWT), Shwachman-Kulczycki (S-K), Brasfield and computed tomography (CT) scores, blood gas analysis and nutritional status of patients were evaluated. Results: Twenty-four patients with a median age of 9.5 years were included. Nocturnal mean SPO2 did not differ according to the severity of lung disease based on PFT However, lowest SPO2 obtained was lower in children with both mild and moderate lung disease compared to normals (87.4% vs. 91.7%, respectively, p=0.009). 95.8% of CF children with normal PFT or mild to moderate lung disease had desaturation events during sleep. Nocturnal mean SPO2 correlated with S-K (Spearman's rho=0.64, p < 0.0001), Brasfield (Spearman's rho=0.31, p=0.007) and CT scores (Spearman's rho= -0.67, p < 0.0001) as well as PaO2 (Spearman's rho= 0.28, p = 0.021), SaO(2) (Spearman's rho=0.28, p= 0.023), z-score of weight (Spearman's rho= 0.23, p= 0.20) and height (Spearman's rho = 0.20, p = 0.30), there was no correlation with 6MWT Conclusions: In CF children with normal PFT or mild-to-moderate lung disease, nocturnal oxygenation may correlate with S-K, Brasfield and CT scores as well as PaO2, SaO(2), z-score of weight and height.
Keywords: cystic fibrosis; child; sleep hypoxemia; desaturation; Shwachman-Kulczycki scores; computed tomography scores; PULMONARY-DISEASE; EXERCISE; DESATURATION; HYPOXEMIA; RELIABILITY; OXIMETRY; ADULTS; STEP